A Bibliometric Analysis of Social Media in Marketing: Mapping Research Trends, Topics, and Keywords from 2019-2024 - Nafisah Arinilhaq; Indah Fatmawati (FAKULTAS DAKWAH UIN SALATIGA, 2025)
The study investigates scholarly publications to identify dominant themes, keyword occurrences, and citation networks related to social media marketing. This study used VOS Viewer and RStudio. The findings indicate that